MANAJEMEN PEMBINAAN ORGANISASI CABANG OLAHRAGA ATLETIK DALAM PRESTASI ATLET DI PASI KABUPATEN PATI - Dwi Nugroho, Yusuf; Rumini, Rumini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the management of athletic sports organization development in improving athletes' achievements at the Athletics Association of Indonesia (PASI) Pati Regency. The study was motivated by the importance of effective organizational management in supporting athlete development programs and sustaining sports achievements. A qualitative descriptive approach was employed, utilizing SWOT analysis as the primary analytical framework. The research participants consisted of the chairman of PASI Pati Regency, administrators, coaches, and athletes. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data presentation, conclusion drawing, and SWOT analysis techniques. The findings revealed that PASI Pati Regency possesses several strengths, including the commitment of administrators and coaches, sustainable development programs, and athletes' competitive achievements at the provincial level. However, weaknesses were identified in terms of limited funding and inadequate training facilities. Opportunities for organizational development include support from local government, the availability of young athletic talents, and participation in various competitions. Meanwhile, threats arise from increasing competition among regions and limited supporting resources. The SWOT analysis indicated that strategies such as optimizing athlete development programs, improving human resource quality, strengthening partnerships with stakeholders, and enhancing training facilities are essential for future development. In conclusion, the management of athlete development at PASI Pati Regency has been implemented fairly well; however, improvements in funding, facilities, and collaborative partnerships are still required to achieve sustainable athletic performance enhancement.